Implementasi Manajemen Kinerja Sebagai Alat Strategi Organisasi Dalam Peningkatan Kinerja Karyawan - Muhammad Hanif Alwani; Ayna Nur Rohmah; Anggit Dian Permana; Kusuma Erma Dana (Jurnal Riset Multidisiplin Edukasi, 2026)
This literature review explores the metamorphosis of performance management from conventional evaluative mechanisms into vital organizational strategic instruments within the global competitive era. The research analyzes academic literature spanning 2021-2025 through thematic content analysis approach to identify implementation dimensions of performance management within contemporary organizational contexts. Findings reveal that strategic performance management encompasses four fundamental pillars: strategic planning aligned with corporate vision, technology-based continuous real-time monitoring, adaptive competency development responsive to industrial dynamics, and transparent objective metric-based evaluation. High-performance human resource management practices demonstrably catalyze organizational change readiness through affective commitment mechanisms, with healthy hierarchical culture serving as a significant moderator in effectiveness reinforcement. Digital transformation introduces innovative paradigms through administrative process automation, predictive analytics implementation for performance trend anticipation, and individual development intervention personalization. Transformational leadership synergizes with constructive organizational culture to accelerate collective performance optimization. Holistic retention strategies integrate evaluative transparency, contribution-based proportional compensation systems, continuous developmental investment, and effective organizational communication. Comprehensive implementation necessitates top management strategic commitment, innovative technology adoption, multi-level transformational leadership cultivation, and learning culture formation to achieve sustainable competitive advantage.